2020
DOI: 10.1161/circresaha.119.315804
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging Provides Detailed Atherosclerotic Plaque Morphology and Reveals Angiogenesis After Carotid Artery Ligation

Abstract: Rationale: Remodeling of the vessel wall and the formation of vascular networks are dynamic processes that occur during mammalian embryonic development and in adulthood. Plaque development and excessive neointima formation are hallmarks of atherosclerosis and vascular injury. As our understanding of these complex processes evolves, there is a need to develop new imaging techniques to study underlying mechanisms. Objective: We used tissue clearing and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…2) and has been successfully used to image three-dimensional structures, including intact mouse organs such as the brain, kidney, intestine, eye, and even whole embryos [18,[22][23][24][25]. Recently, Becher et al [26] applied the iDIS-CO technology for 3D profiling of atherosclerotic plaques and arterial remodeling after carotid artery ligation. We optimized iDISCO for mouse atherosclerotic tissue using endothelial cell-specific CD31 antibodies, and we show here for the first time a 3D reconstruction of IP neovascularization in carotid plaques of ApoE −/− Fbn1 C1039G+/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…2) and has been successfully used to image three-dimensional structures, including intact mouse organs such as the brain, kidney, intestine, eye, and even whole embryos [18,[22][23][24][25]. Recently, Becher et al [26] applied the iDIS-CO technology for 3D profiling of atherosclerotic plaques and arterial remodeling after carotid artery ligation. We optimized iDISCO for mouse atherosclerotic tissue using endothelial cell-specific CD31 antibodies, and we show here for the first time a 3D reconstruction of IP neovascularization in carotid plaques of ApoE −/− Fbn1 C1039G+/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, interpretation of the acquired data requires even more experience. To date, the best imaging techniques with the highest resolution, such as microCT and light-sheet microscopy, are still lethal or only applicable to one model ( 137 – 139 ). While in vivo imaging of mice can be achieved by adapting human imaging technologies and vice versa , imaging of zebrafish larvae can be achieved with simple microscopes.…”
Section: Discussionmentioning
confidence: 99%
“…Using light-sheet microscopy to study plaque formation in different blood vessels has very recently been suggested by Becher et al 19 . Optical cross-sections obtained by LSFM were shown to correlate well with traditional histological stained tissue sections.…”
Section: Discussionmentioning
confidence: 99%
“…LSFM is a non-destructive imaging technique that makes paraffin-embedding and sectioning unnecessary, requiring little hands-on sample preparation time and offering great scaling capability (Supplemental Tables 1 , 2 ). The technology has been applied to image parts of the cardiovascular system before 13 , 16 – 18 Becher et al have recently shown that this imaging technology can successfully be applied to detect plaque in brachiocephalic, carotid and radial arteries 19 . However, 3D light sheet imaging generates large data volumes that pose unique and so far unanswered challenges for rapid image analysis in particular in preclinical drug discovery studies.…”
Section: Introductionmentioning
confidence: 99%